TFEB Promotes Prostate Cancer Progression via Regulating ABCA2-Dependent Lysosomal Biogenesis - Zhu, Xuejin; Zhuo, Yangjia; Wu, Shulin; Chen, Yanfei; Ye, Jianheng; Deng, Yulin; Feng, Yuanfa; Liu, Ren; Cai, Shanghua; Zou, Zhihao; Wang, Bin; Wu, Chin-Lee; et al. (Frontiers in Oncology, 2021)
Transcription factor EB (TFEB), a member of the MiT family, is dysregulated in different cancers and exerts specific biological functions within the tumor microenvironment. Downregulation of TFEB induces macrophage polarization in the TME and promotes tumor progression. However, the biological role and clinical significance of TFEB in prostate cancer (PCa) remain unknown. This study aimed to identify the role of TFEB in PCa and its potential clinical value. We explored TFEB expression in PCa using public databases and verified its prognostic value using immunohistochemistry in PCa tissue samples. The results revealed that TFEB expression was up-regulated in PCa tissues and was associated with cancer metastasis. Next, overexpression of TFEB promoted PCa cell malignant behavior in in vivo and in vitro experiments. RNA-sequencing and bioinformatics analysis showed high expression of TFEB promoted lysosomal biogenesis and knockdown of TFEB expression decreased the number of lysosomes. Furthermore, the ATP-binding cassette transporter A2 (ABCA2) was identified as a target gene of TFEB, which was verified using the cleavage under targets and release using nuclease (CUT&RUN) assay and qRT-PCR. Silencing of ABCA2 reduced lysosomal biogenesis and decreased matrix metalloproteinases expression, which reduced PCa cell invasion and migration in the tumor microenvironment. Our study suggests that TFEB promotes PCa progression by regulating ABCA2 through lysosomal biogenesis and may serve as a prognostic factor or as a potential therapeutic target of PCa.